Is Placental Mitochondrial Function a Regulator that Matches Fetal and Placental Growth to Maternal Nutrient Intake in the Mouse? - Marcos R Chiaratti; Sajida Malik; Alan Diot; Elizabeth Rapa; Lorna Macleod; Karl Morten; Manu Vatish; Richard Boyd; Joanna Poulton (PLoS ONE)
Background Effective fetal growth requires adequate maternal nutrition coupled to active transport of nutrients across the placenta, which, in turn requires ATP. Epidemiological and experimental evidence has shown that impaired maternal nutrition in utero results in an adverse postnatal phenotype for the offspring. Placental mitochondrial function might link maternal food intake to fetal growth since impaired placental ATP production, in response to poor maternal nutrition, could be a pathway linking maternal food intake to reduced fetal growth. Method We assessed the effects of maternal diet on placental water content, ATP levels and mitochondrial DNA (mtDNA) content in mice at embryonic (E) day 18 (E18). Females maintained on either low- (LPD) or normal- (NPD) protein diets were mated with NPD males. Results Fetal dry weight and placental efficiency (embryo/placental fresh weight) were positively correlated (r = 0.53, P = 0.0001). Individual placental dry weight was reduced by LPD (P = 0.003), as was the expression of amino acid transporter Slc38a2 and of growth factor Igf2. Placental water content, which is regulated by active transport of solutes, was increased by LPD (P = 0.0001). However, placental ATP content was also increased (P = 0.03).